BURNOUT IN DOCTORS WORKING IN TERTIARY CARE HOSPITAL IN PESHAWAR, PAKISTAN - Hussain, Shahzadi Saima; Qazi, Qudsia; Bawar, Shandana (Journal of Postgraduate Medical Institute, 2022)
Objective: To determine the frequency of burnout in postgraduate doctors working in a Tertiary Care Hospital in Peshawar, Pakistan Methodology: This cross-sectional study was conducted in tertiary care hospital in Peshawar from June 2019 to December 2019. Using the Non-probability convenient sampling technique 252 doctors from different specialties participated in this study, by filling out the questionnaire. The questionnaires had three parts, questions related to Socio-demographic data, questions related to the workplace, and Maslach Burnout Inventory (MBI). For analysis of data related to MBI, we added up each component (emotional exhaustion, depersonalization, and reduced personal accomplishment). The values obtained were interpreted according to reference values of the Center of Advanced Studies on Burnout Syndrome (NEPASB). Data was analysed using SPSS 20. Results: In this study, out of these 252 doctors 25.39% were having high burnout while 32.93% were found to be at high risk of burnout. On the MBI scale 34.92% % showed a high score for Emotional exhaustion, 95.23 % of doctors scored high in Depersonalization, and 95.63% % scored low in Personal accomplishment. Amongst specialties burnout score was highest in orthopedics (80.14) followed by obstetricians and Gynecologists (75.35). Burnout was reported in 68.85% of young doctors aged 25-30, females (71.58%) were affected with burnout more as compared to male gender. Conclusion: This study concluded that about one-third of doctors were at high risk of developing burnout, while 25% were already affected by burnout.